Injuries in strength training: review and practical application - Javier Butragueño; Pedro José Benito; Nicola Maffulli (Asociación Española de Ciencias del Deporte, 2014)
Purpose: This systematic review examines what is known about injuries in strength training. Methods: A systematic search was performed in PubMed and SportDiscus. Studies were included if they examined powerlifters, weightlifters, strongman athletes, bodybuilding athletes, individuals who undertook recreational weight training or weight training to complement athletic performance. Exposure variables were incidence, severity and body part injury. Results: After examining 1214 titles and abstracts, 62 articles were identified as potentially relevant. Finally, 11 were included in this systematic review. Conflicting results were reported on the relationships between injury definition and incidence or severity recorded.  The lower back followed by the shoulder and knee are the most frequently affected areas in strength sports. Conclusion: Strength training is safe. However, the variety of injury definitions has makes it difficult to compare different studies in this field. New styles of reporting injuries have appeared, and could make increases these ratios. If methodological limitations in measuring incidence rate and severity injuries can be resolved, more work can be conducted to define the real incidence rate, compare it with others sports, and explore cause and effect relationships in randomized controlled trials.